2010
DOI: 10.1631/jzus.b1000081
|View full text |Cite
|
Sign up to set email alerts
|

Cordycepin induces apoptosis by enhancing JNK and p38 kinase activity and increasing the protein expression of Bcl-2 pro-apoptotic molecules

Abstract: Abstract:Objective: To explore the molecular mechanism by which cordycepin inhibits cell proliferation and induces apoptosis of human colorectal cancer cells. Methods: Cell counting and MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfopheny)-2H-tetrazolium, inner salt) method were used to monitor the effects of cordycepin on cell proliferation. Flow cytometry (FCM) was used to analyze the effects of cordycepin on the cell cycle progress. Annexin V-fluorescein isothiocyanate (FITC) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…et al, 2015). Meanwhile, studies have demonstrated that an increased expression of pro-apoptotic Bax family proteins and a decreased expression of anti-apoptotic Bcl-2 family proteins were connected with the process of cell apoptosis (He et al, 2010;Yu et al, 2010). In the whole pathway system, Bax and Bcl-2 are the relevant downstream indexes of PI3K/Akt signaling pathway (Gao et al, 2010) and their regulation can induce the activity of caspase-9, so we evaluated the protein expression of Akt, p-Akt, caspase-9, Bax, and Bcl-2 to elucidate the possible mechanism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2015). Meanwhile, studies have demonstrated that an increased expression of pro-apoptotic Bax family proteins and a decreased expression of anti-apoptotic Bcl-2 family proteins were connected with the process of cell apoptosis (He et al, 2010;Yu et al, 2010). In the whole pathway system, Bax and Bcl-2 are the relevant downstream indexes of PI3K/Akt signaling pathway (Gao et al, 2010) and their regulation can induce the activity of caspase-9, so we evaluated the protein expression of Akt, p-Akt, caspase-9, Bax, and Bcl-2 to elucidate the possible mechanism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al [10] suggested that cordycepin might inhibit the migration and invasion in human prostate cancer cells via the inactivation of Akt. He et al [11] confirmed that cordycepin could induce cell apoptosis in human colorectal cancer cells through increasing the expression of pro-apoptotic Bcl-2 protein and enhancing the activity of JNK and p38 kinase. Besides, cordycepin has been shown to inhibit the growth of mouse lung carcinoma cells via stimulating adenosine A3 receptors [12] or play an antimetastatic role inhibiting the invasiveness of mouse melanoma cells.…”
Section: Introductionmentioning
confidence: 97%
“…suggested that cordycepin might inhibit the migration and invasion in human prostate cancer cells via the inactivation of Akt. He et al . confirmed that cordycepin could induce cell apoptosis in human colorectal cancer cells through increasing the expression of pro‐apoptotic Bcl‐2 protein and enhancing the activity of JNK and p38 kinase.…”
Section: Introductionmentioning
confidence: 99%
“…Some suggestions were also made that increase in c-Jun N-terminal Kinase(JNK), P38 kinase activity and protein expression levels of Bcl-2 pro apoptotic molecules played a role in cell apoptosis. The conclusion was drawn that inhibition of cell proliferation and further apoptosis of SW480 and SW620 cells were induced by cordycepin [7]. Similar action of cordycepin was also demonstrated in gallbladder cancer cells in vitro with its additional effect in down regulation of multidrug resistance (MDR) expression [8].…”
Section: Effect Of Cs On Various Cancer Cellsmentioning
confidence: 71%
“…Inhibition of human colorectal cancer cells with cordycepin was demonstrated by Wei HE and team in Zhejiang University of Technology using SW480 and SW620 cells in vitro [7]. Different concentrations (1, 10, 100, 1000 µmol/L against the control with 0.2% (v/v) dimethyl sulfoxide medium) of cordycepin treatment were given in cell culture after 24 hours of its incubation, cells were counted after 24, 48 and 72 hours using trypan blue.…”
Section: Effect Of Cs On Various Cancer Cellsmentioning
confidence: 99%